2012
DOI: 10.1002/jcop.21485
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Alcohol Use in Youth Aged 12–17 Years Using the Strategic Prevention Framework

Abstract: Although evidence‐based interventions to reduce underage drinking have been identified, dissemination into ‘real‐world’ communities remains challenging. The purpose of this community‐based translational research is to test SAMHSA's Strategic Prevention Framework (SPF) as a model for such dissemination and evaluate its effect on alcohol use by youth aged 12–17. From 2001–2009 in Eau Claire, Wisconsin we used the SPF to assess community needs and implement a comprehensive strategy of evidence‐based programs targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This is reflected in the fact that those programs which have been effective have had clearly defined messages and interventions for each target group; for example, the implementation of SPF in Eau Claire County (Eddy et al, 2012); and in the conclusion by those who have evaluated enforcement approaches to underage supply that there is a need to concurrently address formal and informal supply (SchellemanOffermans et al, 2012, Flewelling et al, 2013.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is reflected in the fact that those programs which have been effective have had clearly defined messages and interventions for each target group; for example, the implementation of SPF in Eau Claire County (Eddy et al, 2012); and in the conclusion by those who have evaluated enforcement approaches to underage supply that there is a need to concurrently address formal and informal supply (SchellemanOffermans et al, 2012, Flewelling et al, 2013.…”
Section: Discussionmentioning
confidence: 97%
“…The Eau Claire County intervention included youth programs (in schools and in the community-including goal setting, refusal skills and social norms); parent programs (designed to increase parental disapproval of alcohol use and rule enforcement); and community programs (community awareness, policy change). Data from middle school and high school surveys showed significant declines in alcohol use, binge drinking, and perceived ease of obtaining alcohol; and a significant increase in perceived parental disapproval of alcohol use (Eddy et al, 2012).…”
Section: Targeting Whole-of-communitymentioning
confidence: 98%
“…Evaluation research reveals that evidence-based youth programs successfully aid in the development of positive behaviors among adolescents (Eddy, et al, 2012;Holleran Steiker, Hopson, Goldbach, & Robinson, 2014;Norton & Watt, 2014). Previous research has documented key factors of successful youth programming.…”
Section: Evidence-based Youth Programming and Youth Engagementmentioning
confidence: 99%
“…The Strategic Prevention Framework (SPF) is a five-phase model that supports the use of comprehensive or multi-component community-based approaches (Eddy et al, 2012; Substance Abuse and Mental Health Services Administration, 2011). The SPF phases include assessment, capacity, planning, implementation, and evaluation, which work in concert to promote cultural competency and sustainability of community-based prevention efforts.…”
Section: Strategic Prevention Frameworkmentioning
confidence: 99%
“…In a cross-site evaluation, Florin and colleagues (2012) found that as part of a comprehensive community intervention, policy, media, and enforcement related prevention efforts were associated with improvements in their respective outcomes. Another study found that implementing the SPF resulted in decreases in students’ past 30-day alcohol use, binge drinking, and ease of obtaining alcohol over time (Eddy et al, 2012). Although the Eddy et al study showed improvements in underage-drinking related outcomes, similar prevention outcome findings in other communities have not been published in the peer-reviewed literature.…”
Section: Strategic Prevention Frameworkmentioning
confidence: 99%